MODEL KEPEMIMPINAN INKLUSIF DALAM MENDORONG PARTISIPASI USTADZ, SANTRI, DAN WALI SANTRI DALAM PENGAMBILAN KEBIJAKAN DI PONDOK PESANTREN AL ADZKAR PAMULANG KOTA TANGERANG SELATAN - Firmansyah; Nuryati Djihadah; Neng Nurhemah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze inclusive leadership practices, the relationship between leaders and ustadz, santri, and guardians, as well as the participation opportunities opened by leaders in the policy-making process at Al Adzkar Islamic Boarding School, Pamulang, South Tangerang City. This study uses a qualitative approach with a case study methodology. The population or target of the study includes the residents of Al Adzkar Islamic Boarding School, consisting of the boarding school leadership, principal, ustadz/teachers, students, and guardians. The sample or informants were selected using a purposive sampling technique based on their involvement and understanding of the leadership and policy-making process at the boarding school. Data collection techniques included semi-structured in-depth interviews, participant observation, open-ended questionnaires, and documentation studies. The researcher acted as the primary instrument, supported by interview guides, observation sheets, open-ended questionnaires, field notes, and documentation checklists. Data validity was checked through source and technique triangulation. Data were analyzed through data presentation, data reduction and coding, thematic category grouping, interpretation of findings, and drawing conclusions. The results showed that inclusive leadership practices were implemented through openness, leader availability, easy access to leaders, deliberation, collaboration, role models, and empowerment of Islamic boarding school residents. The relationship between leaders and ustadz/teachers was collaborative and based on communication, trust, and respect for competence. The relationship between leaders and students was one of guidance, role models, and communication, while the relationship with students' guardians demonstrated a partnership pattern in supporting students' education and development. Space for participation was opened through deliberation or syuro forums, coordination meetings, student organizations, direct communication, digital media, and informal discussions. Although space for participation was available, the involvement of students and their guardians in strategic decision-making was not fully equitable. The final decision rests with the Kyai to ensure policies align with the vision, mission, Islamic values, and traditions of the Islamic boarding school.